INOVASI STRATEGI PEMBEAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATAKNA MUTU PEMBELAJARAN - Neni Neni (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2021)
One of the challenges currently faced by Islamic education is the declining level of public trust in educational institutions with Islamic nuances. This happens because of the decline in morals in the midst of the development of the current era. Many think that Islamic educational institutions have failed as agents who play an important role in building a civilization. However, it is inevitable that many stakeholders say that the most important factor is that the strategy used by Islamic education is not right. Learning strategies play an important role in determining the success of education and the personal formation of students as a whole and comprehensively. Without the right strategy, the learning process will not run effectively and efficiently. Therefore, the teacher as the spearhead of education has an important role in the learning process. Strategic innovation in learning will prepare students as a quality generation of the nation to enter the era of globalization which is full of various challenges and very complex problems.